Endoscopic characteristics and high-risk background mucosa factors of early gastric cancer after helicobacter pylori eradication: a single-center retrospective study - Wei, Yali; Min, Congcong; Zhao, Chongguang; Li, Yubei; Wang, Xiaowei; Jing, Xue; Yu, Yanan; Li, Xiaoyu; Yin, Xiaoyan (Frontiers in Oncology, 2023)
Purpose Gastric cancer still develops after successful Helicobacter pylori(Hp)eradication. In this study, we aimed to explore the characteristics and risks of mucosal factors. Methods A total of 139 early gastric cancers (EGC) diagnosed in 133 patients after successful eradication from January 2016 to December 2021 were retrospectively included in the Hp-eradication EGC group and 170 EGCs diagnosed in 158 patients were included in the Hp-positive EGC group. We analyzed the clinical, pathological, and endoscopic characteristics between the two groups to identify the features of EGC after Hp eradication. Another 107 patients with no EGC after Hp eradication were enrolled in a Hp-eradication non-EGC group. The background mucosal factors between the Hp-eradication EGC group and the Hp-eradication non-EGC group were compared to analyze the high-risk background mucosal factors of EGC after eradication. In addition, we divided the EGC group after Hp eradication into IIc type and non-IIc type according to endoscopic gross classification to assess the high-risk background factors of IIc-type EGC after Hp eradication. Results The endoscopic features of EGC after Hp eradication included location in the lower part of the stomach (p=0.001), yellowish color (p= 0.031), and smaller size (p=0.001). The moderate/severe gastric atrophy (GA), intestinal metaplasia (IM) in the corpus, severe diffuse redness, and map-like redness were risk factors for EGC after eradication (p=0.001, p=0.001, p=0.001, and p= 0.005, respectively). The Kyoto classification total score in the EGC group was higher than the non-EGC group (4 vs.3 p<0.001). A multivariate analysis revealed that depressed erosion (OR=3.42, 95% CI 1.35-8.65, p= 0.009) was an independent risk factor for IIc-type EGC after Hp eradication. Conclusion EGC after eradication are smaller and yellowish lesions located in the lower part of the stomach. The risk background mucosal factors include moderate/severe GA, IM in the corpus, severe diffuse redness, and map-like redness. The Kyoto classification total score of 4 or more after successful eradication treatment might indicate EGC risk. In addition, the IIc-type EGC should be cautioned in the presence of depressed erosion after Hp eradication.